2000
DOI: 10.1016/s0378-4371(00)00444-1
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary minority game with heterogeneous strategy distribution

Abstract: We present detailed numerical results for a modified form of the so-called Minority Game, which provides a simplified model of a competitive market. Each agent has a limited set of strategies, and competes to be in a minority. An evolutionary rule for strategy modification is included to mimic simple learning. The results can be understood by considering crowd formation within the population.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…In fact, the main motivation for the introduction of time-dependent random walks in [13] was its applicability in the flourishing field of complex adaptive systems. In the well-studied model of the minority game (MG) [14], and its evolutionary version (EMG) [15] (see also [16][17][18][19][20][21][22][23][24][25][26][27][28]), it was found that the winning probabilities of the agents display a periodic behavior in time. This implies that the survival probabilities of the agents are well-described by a model of a periodic time-dependent random walk with an absorbing boundary [13].…”
mentioning
confidence: 99%
“…In fact, the main motivation for the introduction of time-dependent random walks in [13] was its applicability in the flourishing field of complex adaptive systems. In the well-studied model of the minority game (MG) [14], and its evolutionary version (EMG) [15] (see also [16][17][18][19][20][21][22][23][24][25][26][27][28]), it was found that the winning probabilities of the agents display a periodic behavior in time. This implies that the survival probabilities of the agents are well-described by a model of a periodic time-dependent random walk with an absorbing boundary [13].…”
mentioning
confidence: 99%
“…The Genetic Model represents an abstract model of a population competing for a limited resource and as such it often discussed in the context of financial markets [3,4,8,9,12,13,26]. In such a context, however, it does not seem realistic that the agents trade at every time step.…”
Section: B the Grand Canonical Genetic Modelmentioning
confidence: 99%
“…[4,5,6] Thus, in order to succeed in a competitive society the agent must take extreme positions. This behavior can be explained by the market impact of the agents' own actions which largely penalizes the cautious agents.…”
Section: Phenomenology Of the Evolutionary Minority Gamementioning
confidence: 99%